Keluhan Kesehatan Subjektif Akibat Pajanan Pestisida pada Petani Palawijaya di Kecamatan Dempo Utara Pagar Alam - Imelda Gernauli Purba; Inoy Trisnaini; Rahmatillah Razak (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2023)
Latar belakang: Pagar Alam merupakan daerah yang penduduknya mengandalkan pertanian sebagai mata pencaharian utama. Hal ini menyebabkan tingginya penggunaan pestisida pertanian. Berdasarkan survei awal diketahui bahwa 60 % petani mengalami keluhan pusing setelah beberapa jam melakukan penyemprotan. Tujuan penelitian ini adalah menganalisis hubungan faktor-faktor risiko pajanan dengan keluhan kesehatan subjektif pada petani penyemprot pestisida.Metode: Jenis penelitian ini adalah observasional analitik dengan desain Cross-sectional. Variabel independen terdiri dari lama penyemprotan, frekuensi penyemprotan, masa kerja, jumlah jenis pestisida sekali mencampur. Variabel dependen adalah keluhan kesehatan subjektif yang terdiri dari mudah lelah, gelisah, sakit kepala, penglihatan kabur, produksi air ludah meningkat, sering mual, otot terasa lemah, gatal pada kulit, sesak nafas dan batuk-batuk. Sampel sebanyak 120 petani penyemprot pestisida di Kecamatan Dempo Utara diambil secara cluster sampling. Pengumpulan data dilakukan melalui wawancara dengan menggunakan kuesioner dan observasi menggunakan checklist. Pengolahan dan analisis data menggunakan bantuan software SPSS, dan analisis data menggunakan uji statistik Chi-Square. Hasil: Hasil penelitian menunjukkan keluhan kesehatan subjektif yang dialami responden akibat faktor resiko pajanan pestisida adalah mudah lelah, gelisah, sakit kepala, penglihatan kabur, produksi air ludah meningkat, sering mual, otot terasa lemah, gatal pada kulit, sesak nafas dan batuk-batuk. Hasil analisis statistik menunjukkan kemaknaan hubungan antara lama penyemprotan dengan keluhan mudah lelah (0,026), masa kerja dengan keluhan sakit kepala (0,009), jumlah jenis pestisida dengan keluhan sakit kepala (0,047), lama penyemprotan dengan keluhan penglihatan kabur (0,003)Simpulan: Faktor risiko pajanan berhubungan dengan keluhan kesehatan subjektif diataranya lama penyemprotan dengan keluhan mudah lelah, masa kerja dengan keluhan sakit kepala, jumlah jenis pestisida dengan keluhan sakit kepala, lama penyemprotan dengan keluhan penglihatan kabur. ABSTRACT Title: Subjective Health Complaints due to Pesticide Exposure to Secondary Crops Farmers in Dempo Utara District, Pagar AlamBackground: Pagar Alam is an area whose residents rely on agriculture as their main livelihood. This causes the high use of agricultural pesticides. Based on the preliminary survey, it was found that 60% of farmers experienced complaints of dizziness after several hours of spraying. The purpose of this study was to analyze the relationship between exposure risk factors and subjective health complaints among farmers spraying pesticides. Method: This type of research was analytic observational with a cross-sectional design. The independent variables consist of duration of spraying, frequency of spraying, working period, number of types of pesticides mixed at once. The dependent variable was subjective health complaints consisting of fatigue, anxiety, headaches, blurred vision, increased saliva production, frequent nausea, muscle weakness , itching of the skin, shortness of breath and coughing. A sample of 120 farmers spraying pesticides in Dempo Utara District was taken by cluster sampling. Data collection was carried out through interviews using a questionnaire and observation using a checklist. Data processing and analysis using SPSS software assistance, and analysis using the Chi-Square statistical. Result: The results showed that the subjective health complaints experienced by respondents were fatigue, anxiety, headaches, blurred vision, increased saliva production, frequent nausea, muscle weakness, skin itching, shortness of breath and coughing. The results of the statistical analysis showed a significant relationship between the duration of spraying and complaints of fatigue (0.026), length of work and complaints of headaches (0.009), the number of types of pesticides and complaints of headaches (0.047), duration of spraying and complaints of blurred vision (0.003).Conclusion: Exposure risk factors are related to subjective health complaints including duration of spraying with complaints of fatigue, length of work with complaints of headaches, number of types of pesticides with complaints of headaches, duration of spraying with complaints of blurred vision.